1989
DOI: 10.1002/apmc.1989.051660103
|View full text |Cite
|
Sign up to set email alerts
|

Structure and molecular dynamics of highly mobile polymer membranes

Abstract: The function of lipid bilayer membranes crucially depends on their mobility and their ability to incorporate components that, e.g.. can change molecular order and dynamics or form channels. Since polymerization increases the stability of model membranes at the expense of their mobility a compromise must be sought. Therefore. the effect of different polymerization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…reported that UV polymerization of vesicles of diocta­decadienoyl­ammonium bromide, a cross-linkable lipid, caused a 4-fold reduction in D which was attributed to a low number-average degree of polymerization ( X n ). Diacetylene lipids, both pure and mixed with nonpolymerizable, fluid-phase lipids, have been the subject of several studies. Upon exposure to a high dose of UV irradiation, pure bis-diacetylene lipid bilayers are highly cross-linked which results in D ≈ 0 on the time scale of a FRAP measurement. , Lower UV doses, however, produce partially polymerized bilayers in which restricted lateral diffusion of coincorporated, nonpolymerizable lipids is observed. , Fahmy et al reported that thermal polymerization of bilayers composed of a zwitterionic lipid with a methacryloyl group in one tail caused a 500-fold increase in the time constant for fluorescence bleaching recovery. Kölchens et al examined diffusion in membranes composed of mono- and bis-acryloyl phosphatidyl­cholines that were polymerized using thermal initiation.…”
Section: Introductionmentioning
confidence: 99%
“…reported that UV polymerization of vesicles of diocta­decadienoyl­ammonium bromide, a cross-linkable lipid, caused a 4-fold reduction in D which was attributed to a low number-average degree of polymerization ( X n ). Diacetylene lipids, both pure and mixed with nonpolymerizable, fluid-phase lipids, have been the subject of several studies. Upon exposure to a high dose of UV irradiation, pure bis-diacetylene lipid bilayers are highly cross-linked which results in D ≈ 0 on the time scale of a FRAP measurement. , Lower UV doses, however, produce partially polymerized bilayers in which restricted lateral diffusion of coincorporated, nonpolymerizable lipids is observed. , Fahmy et al reported that thermal polymerization of bilayers composed of a zwitterionic lipid with a methacryloyl group in one tail caused a 500-fold increase in the time constant for fluorescence bleaching recovery. Kölchens et al examined diffusion in membranes composed of mono- and bis-acryloyl phosphatidyl­cholines that were polymerized using thermal initiation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the method described by Duda et al and from the photograph, an average monolayer is estimated to be 32 Å thick, because the thickness of the arbitrary 20 layers is 640 Å. These findings suggest that the structure of LB films of phospholipid-modified polypeptide 3 agrees with the model of polymeric lipids 3 Transmission electron micrograph of a cross-sectional view of the phospholipid-modified polypeptide 3 LB films (30 layers) stained on a PET film plate and imaged at an original 250 000× magnification. …”
Section: Resultsmentioning
confidence: 83%
“…But the dynamic profile seen for standard micelles is superposed by the dynamic restrictions imposed by the polymer backbone as the backbone tends to immobilize the side chain fragments close by [276,386,387]. Whereas the general profile stays the same in polysoaps for "head" geometry as in standard surfactants, i.e., the head groups are the least mobile segments [388,389], polysoaps of "tail end" geometry show a dynamic profile of the surfactant fragments opposite to the one of the monomeric analogues.…”
Section: Dynamic Propertiesmentioning
confidence: 99%